Áramlási terek és államhatárok Közép-Európában : Magyarország történeti térhelyzetének áttekintése - Csüllög, Gábor (Közép-Európai Közlemények, 2012)
The Central European region is one of the most important flow zones in Europe where the migration of peoples has been going on for thousands of years, economic and cultural influences have been spreading and power politics has taken effect. The activeness and continuity of the uninterrupted flow system has been maintained by the empires ruling over the region. When the influence of the empire weakens, the flow zone gets divided up by local state spaces organized at various junctions of the flows, and their various sections are closed down by borders. The region, therefore, has been characterized by a specific dynamics for a long time: within the spaces of the empire, it is the joint effects of the flows that take effect during a long period of time; at a shorter interval, the flows blocked by the borders of the local states “tighten” the region. The local state spaces, at the same time, are incapable of counterbalancing steadily the opposite flows. Their existence is connected to the closing flow spaces, which compels them to strengthen their borders continuously, which then leads to isolations and strong clashes within the region. Consequently, the instability of the region divided into small state spaces “pulls in” the growing spaces of great powers over and over again.